FACTORS ASSOCIATED WITH THE UPTAKE OF SAFE MALE MEDICAL CIRCUMCISION AMONG MALES AGED 18 TO 49 YEARS AT MASAKA REGIONAL REFERRAL HOSPITAL. A CROSS-SECTIONAL STUDY. - Kabanda, Gilbert; Anywar, Lydia (Student’s Journal of Health Research Africa, 2023)
Introduction: Objectives: To determine the factors associated with the uptake of Safe Male Medical Circumcision among males aged 18-49 years at Masaka Regional Referral Hospital. Methodology: The study was based on a purposive non-probability sampling method in which 120 were the target but 100 participants fully participated, the study employed a structured questionnaire administered by the researcher and the research assistants to collect data. Results: The majority of participants; 48% were in the 18-24 age group, protestants were 43%, married were 53% and 38% were farmers. Most respondents 40% had attained primary level of education, 68% had support from a female partner, 59% had SMMC as a choice of type of circumcision and 43% chose TMC because of community respect. The majority of the respondents 38% had the perception that uncircumcised men enjoyed sex more than circumcised men, 83% were satisfied with SMC and 42% had personal fear of bleeding. More so, most of the respondents 88% were circumcised from Government facilities, 54% were not referrals from HIV testing facilities and 87% received health education before SMC services. Conclusion: The majority of respondents had female partnership support for VMMC services and also the majority of the respondents were not referrals from HIV testing facilities. Clients who had Medical circumcision were satisfied with the services and ready to recommend them to their friends and sons. Recommendations: The Ministry of Health needs to plan on how to provide continuous health education about male circumcision and this should be done mostly through women and different media in different languages understood by local communities to overcome the beliefs about traditional circumcision to SMC. The Ministry of Health should also empower HIV testing units to facilitate HIV testing services and health education on SMC which shall increase referrals for the services.